2021
DOI: 10.1002/advs.202004222
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Genome Sequence of Synthesized Allopolyploids in Cucumis Reveals Insights into the Genome Evolution of Allopolyploidization

Abstract: The importance of allopolyploidy in plant evolution has been widely recognized. The genetic changes triggered by allopolyploidy, however, are not yet fully understood due to inconsistent phenomena reported across diverse species. The construction of synthetic polyploids offers a controlled approach to systematically reveal genomic changes that occur during the process of polyploidy. This study reports the first fully sequenced synthetic allopolyploid constructed from a cross between Cucumis sativus and C. hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 123 publications
1
17
0
Order By: Relevance
“…The reactivation of LTRs (Long Terminal Repeats) in resynthesized hexaploid wheat produces alterations in the expression of neighboring genes [ 303 , 304 ]. Similar results were observed in different species such as synthetic Arabiposis polyploids [ 22 ], synthetic Cucumis polyploids [ 287 ], or Gossypium [ 305 ], among others. TEs can also experience an increase in copy number following the hybridization, as it has been reported in tobacco [ 306 ] or Brassica [ 307 ].…”
Section: Readjustments Of the Merged Genomessupporting
confidence: 83%
See 1 more Smart Citation
“…The reactivation of LTRs (Long Terminal Repeats) in resynthesized hexaploid wheat produces alterations in the expression of neighboring genes [ 303 , 304 ]. Similar results were observed in different species such as synthetic Arabiposis polyploids [ 22 ], synthetic Cucumis polyploids [ 287 ], or Gossypium [ 305 ], among others. TEs can also experience an increase in copy number following the hybridization, as it has been reported in tobacco [ 306 ] or Brassica [ 307 ].…”
Section: Readjustments Of the Merged Genomessupporting
confidence: 83%
“…For example, in the new synthetic allopolyploid Cucumis sativus × C. hystryx drastic changes at genomic level emerge rapidly after hybridization, while others occur in later generations at a slower rate. The study has revealed that the C. sativum subgenome is dominant, preserving more sequences and showing a higher expression level than the C. hystryx genome [ 287 ]. However, in tetraploid cotton, downregulation of the homoeologous gene copies of the submissive genome is mediated by both, cis- and trans-regulatory elements from the dominant genome [ 288 ].…”
Section: Readjustments Of the Merged Genomesmentioning
confidence: 99%
“…Gene expression was affected by the number and distance of nearby TEs [ 56 ]. The subgenome with the greatest TE density had a relatively high probability of gene loss and inactivation and a weak overall expression level [ 57 ]. The number of TEs in B. oleracea was slightly greater than that in B. rapa , which may also provide an explanation for the bias of MBD gene expression in B. napus .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the acquisition of high-throughput markers is the key to comprehensively evaluate REs in the overall genome in Populus . Recently, using genome sequencing and high-precision polyploid genome assembly ( Zhou et al, 2020 ; Yu et al, 2021 ) provides technical support for the acquisition of high-throughput SNPs, which is expected to solve the problem.…”
Section: Discussionmentioning
confidence: 99%